MANAGEMENT OF HYPERTENSIVE DISORDERS IN PREGNANCY AMONG PATIENTS OF DIFFERENT HOSPITALS IN DISTRICT PESHAWAR - Anjum, Zahin; Ali, Shaista; Rahat, Amina; Chishti, Rabia; Yousaf , Faryal; Yousaf, Sumbla (Annals of Allied Health Sciences, 2023)
Objective: To determine the frequency of hypertensive disorders among pregnant women attending different hospitals in Peshawar. Material & Methods: A total of 130 pregnant women through non-probability convenient sampling technique were recruited. After seeking written consent from individual participants, a predesigned questionnaire was filled. Data was collected and analyzed by using SPSS version 16. Results: Of the total participants, 75 (57.7%) were in the age range of 26-35 years and 73(56.2%) were illiterate. Only 14(10.8%) were observed Hypertensive (> 140mmHg) assessed at the time of first pregnancy test. During pregnancy the frequency of Hypertensive (> 140mmHg) women increased remarkably 105(80.8%). Statistical test showed a significant difference p=0.013 for the hypertensive category distributed in three different stage of pregnancy. It was found that 10(7.7%) women underwent through caesarean section and 2 (1.5%) stillbirth cases were also observed. Conclusion: The management of hypertensive disorders among pregnant women was found sub-optimal.